2001
DOI: 10.1212/wnl.57.10.1929
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the single-day praziquantel therapy for neurocysticercosis

Abstract: In 1996, we described a schedule of single-day therapy with praziquantel for management of neurocysticercosis. This treatment resulted in 90% less total dose and costs and 93% less duration of treatment in comparison with the 2-week regimen, achieving similar clinical efficacy. 1 It also showed similar results compared with albendazole. 2 Recent reports in healthy volunteers have suggested that plasma levels of praziquantel increase with the administration of cimetidine 3 and also with a high-carbohydrate diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 5 publications
0
9
0
3
Order By: Relevance
“…Recently, a single-day scheme was proposed (25 mg/kg at 2 h intervals) leading to a 90% reduction of the direct costs in relation to the traditional scheme and preliminary results were encouraging [8,15,[26][27][28]. The decrease in the number of cysts visualized in neuroimaging studies was similar to that observed in patients receiving longer courses of PZQ at conventional doses [8,15,27,29,30]. However, the parasiticidal results obtained by Pretell and colleagues were unsatisfactory in patients with multiple lesions, in whom all cysts persisted unchanged [31].…”
Section: Anticysticercal Drugsmentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, a single-day scheme was proposed (25 mg/kg at 2 h intervals) leading to a 90% reduction of the direct costs in relation to the traditional scheme and preliminary results were encouraging [8,15,[26][27][28]. The decrease in the number of cysts visualized in neuroimaging studies was similar to that observed in patients receiving longer courses of PZQ at conventional doses [8,15,27,29,30]. However, the parasiticidal results obtained by Pretell and colleagues were unsatisfactory in patients with multiple lesions, in whom all cysts persisted unchanged [31].…”
Section: Anticysticercal Drugsmentioning
confidence: 80%
“…Dexamethasone decreases plasma concentration of PZQ but increases ASOX [26,37]. Food, a high carbohydrate diet, grapefruit juice and cimetidine increase plasma PZQ concentration [26,30,[56][57][58]. Foods rich in fat and cimetidine may also favor ALB absorption.…”
Section: Failure Of Anticysticercal Therapy: Possible Explanationsmentioning
confidence: 99%
“…Currently, albendazole is the drug of choice for antiparasitic therapy (15 mg/kg/day for 7 days with oral steroids) although a single day praziquantel regimen seems equally effective (25 mg/kg, three doses at two hour intervals followed by steroids 6 hours later) [14]. Multiple lesions or subarachnoid cysticercosis require a longer course.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why the biopsies were performed is that the diagnosis remained questionable and the disseminated cysticercosis had not been reported in Korea before. Pharmacological management with the cysticidal drugs praziquantel and albendazole is indicated as they help by reducing the parasite burden 8) . These drugs facilitate the death of the cysts.…”
Section: Discussionmentioning
confidence: 99%